Crystal structure of the co-crystal O-isopropyl phenylcarbamothioate – 4,4′-bipyridine (2/1), C15H17N2OS - Yee, Isabel Pin Tsin *; Tiekink, Edward R. T. * (De Gruyter Open Access, 2018)
C15H17N2OS, triclinic, P¯1 (no. 2), a=5.8595(3) Å, b=9.2967(4) Å, c=14.0545(8) Å, α=83.320(4), β= 89.240(4), γ=74.524(4), V =732.71(7) Å3, Z =2, Rgt(F)=0.0458, wRref(F2)=0.1231, T =100 K.